Phenolic profile of Cydonia oblonga Miller leaves - Oliveira, Andreia P. (2008)
Cydonia oblonga Miller leaves phenolic compounds were analyzed by reversed-phase HPLC/DAD and HPLC/UV. Qualitative and quantitative analysis of phenolics were carried out in a total of 36 samples of quince leaves from three different geographical origins of Northern (Bragança and Carrazeda de Ansiães) and Central Portugal (Covilhã) and three collection months (June, August, and October of 2006). These leaves presented a common phenolic profile composed by nine compounds: 3-O-, 4-O- and 5-O-caffeoylquinic acids, 3,5-O-dicaffeoylquinic acid, quercetin-3-Ogalactoside, quercetin-3-O-rutinoside, kaempferol-3-O-glycoside, kaempferol-3-O-glucoside, and kaempferol-3-O-rutinoside. 5-O-caffeoylquinic acid was the major phenolic compound (36.2%), followed by quercetin 3-O-rutinoside (21.1%). Quince leaves are characterized by higher relative contents of kaempferol derivatives than fruits (pulps, peels, and seeds), especially in what concerns kaempferol-3-O-rutinoside (12.5%). C. oblonga leaves total phenolic content was very high, varying from 4.9 to 16.5 g/kg dry matter (mean value of 10.3 g/kg dry matter), indicating that these leaves can be used as a good and cheap source of bioactive constituents. Significantly differences were observed in 3-O-caffeoylquinic and 3,5-O-dicaffeoylquinic acids contents, according to geographical provenance and harvesting month, suggesting a possible use of these compounds as geographical origin and/or maturity markers.